Propofol Infusion Versus Isoflurane/Nitroglycerine Combination for Controlled Hypotensive Anesthesia in Neurosurgery - Muhammad Saad, Haseebullah Yousuf, Talha Ahmed, Mirwais Khan, Adnan Nabi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The use of hypotensive anesthesia is one of several techniques that have been used to lessen the intraoperative loss of blood and improve visibility in the operative field. A procedure that requires a clear area and little intraoperative bleeding, which can affect the surgeons’ abilities, is Neurosurgery. Objective: The current study aimed to assess how both anesthetics affected tissue perfusion, blood loss, operating field visibility, and extubation time. Settings and Design: A prospective quasi-experiment was used in the design of this clinical trial Practical Implication: The practical implication for choosing between propofol infusion and the isoflurane/nitroglycerine combination for controlled hypotensive anesthesia in neurosurgery includes considering several factors. Firstly, the patient’s individual characteristics and medical history should be taken into account to determine the most suitable anesthesia approach. Secondly, the surgical procedure and the desired level of hypotension required should be evaluated. Thirdly, the availability and expertise of the anesthesia team in managing either method should be considered. Finally, potential side effects and complications associated with each technique should be weighed. Ultimately, a well-informed decision must be made based on these considerations to ensure the safety and efficacy of controlled hypotensive anesthesia in neurosurgery. Patients and Methods: Sixty individuals with ASA I or II were separated into two groups; Group P received both induction and maintenance doses of propofol, while Group I received isoflurane for maintenance with nitroglycerine. Blood loss, heart rate, mean arterial pressure, and the degree of surgical field clarity were all monitored every ten minutes. Results: As opposed to the isoflurane group, the propofol group substantial reduction in blood loss (p=0.01), improved clarity of the surgical field (p=0.002), and reduced time to extubation (p=0.001). Conclusion: Even with the addition of the hypertension medication nitroglycerine to isoflurane, propofol for craniotomy improved surgical conditions and gave a quicker recovery than isoflurane. Keywords: Nitroglycerin, Isoflurane, Propofol, Hypotensive Anesthesia, and Neurosurgery